2007
DOI: 10.1007/s10995-007-0253-9
|View full text |Cite
|
Sign up to set email alerts
|

Infant Feeding Attitudes and Knowledge among Socioeconomically Disadvantaged Women in Glasgow

Abstract: Knowledge and attitude predict breastfeeding initiation in this population. Social network members may influence mothers' feeding choices. This research is important because attitudes and knowledge derived from the IIFAS can be used to develop and evaluate breastfeeding promotion programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
90
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(105 citation statements)
references
References 39 publications
11
90
1
3
Order By: Relevance
“…This is might be due to increase awareness in breastfeeding among young mothers through social networks, media and introduction of benefits of breastfeeding in the academic curriculum. However, few studies reported older maternal age as the predictive factor of breastfeeding intention (Dungy et al, 2008;Forster, McLachlan, & Lumley, 2006;Mitra et al, 2004).The present study showed that higher education was associated with breastfeeding intention among the mothers. This finding is aligned with a study done in the United States (Colaizy, Saftlas, & Morriss, 2012).…”
supporting
confidence: 49%
See 2 more Smart Citations
“…This is might be due to increase awareness in breastfeeding among young mothers through social networks, media and introduction of benefits of breastfeeding in the academic curriculum. However, few studies reported older maternal age as the predictive factor of breastfeeding intention (Dungy et al, 2008;Forster, McLachlan, & Lumley, 2006;Mitra et al, 2004).The present study showed that higher education was associated with breastfeeding intention among the mothers. This finding is aligned with a study done in the United States (Colaizy, Saftlas, & Morriss, 2012).…”
supporting
confidence: 49%
“…Both studies were done by McInnes et al and Humphreys et al reported that previous breastfeeding experience was one of the significant determinants of breastfeeding intention (Dungy, McInnes, Tappin, Wallis, & Oprescu, 2008;Humphreys, Thompson, & Miner, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(20) On the contrary, women with negative attitudes towards breastfeeding are considered to be a main barrier to initiate and to continue breastfeeding. (21) Additionally, maternal positive attitudes towards breastfeeding are associated with continuing to breastfeed longer and have a greater possibility of success (20) . On the contrary, women with negative attitudes towards breastfeeding are considered to be a main barrier to initiate and to continue breastfeeding.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, women with negative attitudes towards breastfeeding are considered to be a main barrier to initiate and to continue breastfeeding. (21) Annually 800,000 deaths of under five children can be potentially prevented by optimal breastfeeding up to 2 years of age. Of these, if the children had been breastfed in first hour of life, up to 22.3% of neonatal death can be prevented.…”
Section: Introductionmentioning
confidence: 99%